2009
DOI: 10.1021/jm901001p
|View full text |Cite
|
Sign up to set email alerts
|

Drug Effects Viewed from a Signal Transduction Network Perspective

Abstract: Understanding how drugs affect cellular network structures and how resulting signals are translated into drug effects holds the key to the discovery of medicines. Herein we examine this cause-effect relationship by determining protein network structures associated with the generation of specific in vivo drug-effect patterns. Medicines having similar in vivo pharmacology have been identified by a comparison of drug-effect profiles of 1320 medicines. Protein network positions reached by these medicines were asce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Such systems modeling approaches may be used to define putative drug targets in HCC and improve efficacy of current therapies [35], [36]. First, it was confirmed that the topological properties (betweeneess, clustering coefficients, assortativity, diameter, and modularity) of the Conserved-Net are significantly non-random, thus more likely to reflect biological node importance [37].…”
Section: Discussionmentioning
confidence: 84%
“…Such systems modeling approaches may be used to define putative drug targets in HCC and improve efficacy of current therapies [35], [36]. First, it was confirmed that the topological properties (betweeneess, clustering coefficients, assortativity, diameter, and modularity) of the Conserved-Net are significantly non-random, thus more likely to reflect biological node importance [37].…”
Section: Discussionmentioning
confidence: 84%
“…The available evidences showed that molecular synergisms can be emerged from different aspects, for example, protein complexes in cell-regulatory systems [42], crosstalk [43-47] and feedback control in the structures of signal pathways [48,49], stimuli-influenced number of molecules (e.g. number of activated enzymes, receptors, channels or transcription factors) [50,51] and gene expression profile [52] in signal transduction process. Thus, from the network target perspective, we can gain a comprehensive understanding of drug synergistic mechanisms on the basis of complex biological systems.…”
Section: Resultsmentioning
confidence: 99%
“…However, the direct connection between the targeting of metabolic and signaling pathways by drugs and the adverse drug reactions that they cause has so far not been systematically studied and is only known for individual cases [16], [17], [18], [19], [20].…”
Section: Introductionmentioning
confidence: 99%